Fitorremediação de solo de terras baixas contendo imidazolinonas - Souto, Kelen Müller (2014)
Herbicides that present residual effect in the soil, preventing or reducing the emergence of weeds, are inputs of great importance to ensure the expected productivity of comercial crops. However, this residual can prejudice the next crops that do not have the tolerance to the active ingredient of these products and the longer they remain in the soil, the probability of leaching is higher, contaminating the environment. In view of the above, this doctorate thesis had as a goal evaluate the possibility of descontamination of rice cultivating soils with residual of the herbicides imazethapyr, imazapic and imazapyr, by the use of potential phytoremediator plants. The present study was divided in four chapters: 1) Phytoremediation in pots containing soil of irrigated rice with residual imidazolinone; 2) Imidazolinone degradation in rhizosphere of plants phytoremediator; 3 Efficiency of Vicia sativa in the remediation of soil contaminated with imazapyr + imazapic depending on soil type and 4) Use of plants in reducing the residual formulated mixtures of imazethapyr + imazapic and imazapyr + imazapic in codição field. Soybean, vetch, jack bean and consortium of white clover and birdsfoot trefoil, are plants that have the ability to remediate soil contaminated with herbicides belonging to the chemical group of the imidazolinone. The degradation of the herbicide imazethapyr, imazapyr and imazapic, is higher in vegetated soil than in bare soil, demonstrating phytoestimulator effect of these plant species under the existing microbiota in the rhizosphere of the same. Vetch is phytoremediation of soil contaminated with formulated mixture of imazapyr + imazapic even in different soil types. The herbicide imazapyr + imazapic causes greater residual effect that imazethapyr + imazapic, under field condition. .